Molecular mechanisms for tumour resistance to chemotherapy - Pan, Shu-Ting; Li, Zhi-Ling; He, Zhi-Xu; Qiu, Jia-Xuan; Zhou, Shu-Feng (Clinical and experimental pharmacology & physiology, 2016)
Summary Chemotherapy is one of the prevailing methods used to treat malignant tumours, but the outcome and prognosis of tumour patients are not optimistic. Cancer cells gradually generate resistance to almost all chemotherapeutic drugs via a variety of distinct mechanisms and pathways. Chemotherapeutic resistance, either intrinsic or acquired, is caused and sustained by reduced drug accumulation and increased drug export, alterations in drug targets and signalling transduction molecules, increased repair of drug‐induced DNA damage, and evasion of apoptosis. In order to better understand the mechanisms of chemoresistance, this review highlights our current knowledge of the role of altered drug metabolism and transport and deregulation of apoptosis and autophagy in the development of tumour chemoresistance. Reduced intracellular activation of prodrugs (e.g. thiotepa and tegafur) or enhanced drug inactivation by Phase I and II enzymes contributes to the development of chemoresistance. Both primary and acquired resistance can be caused by alterations in the transport of anticancer drugs which is mediated by a variety of drug transporters such as P‐glycoprotein (P‐gp), multidrug resistance associated proteins, and breast cancer resistance protein. Presently there is a line of evidence indicating that deregulation of programmed cell death including apoptosis and autophagy is also an important mechanism for tumour resistance to anticancer drugs. Reversal of chemoresistance is likely via pharmacological and biological approaches. Further studies are warranted to grasp the full picture of how each type of cancer cells develop resistance to anticancer drugs and to identify novel strategies to overcome it.